An eddy pathway to marine heatwave predictability off eastern Tasmania - Zhao, Zijie; Holbrook, Neil J.; Oliver, Eric C. J. (Frontiers in Climate, 2022)
A systematic analysis of historical and modelled marine heatwaves (MHWs) off eastern Tasmania has been performed based on satellite observations and a high–resolution regional ocean model simulation, over the period from 1994–2016. Our analysis suggests that the distribution of large and intense mesoscale warm core eddies off northeast Tasmania contribute to the development of MHWs further south associated with changes in the circulation and transports. Importantly, we find that eddy distributions in the Tasman Sea can act as predictors of MHWs off eastern Tasmania. We used self-organising maps to distinguish sea surface height anomalies (SSHA) and MHWs into different, but connected, patterns. We found the statistical model performs best (precision ~ 0.75) in the southern domain off eastern Tasmania. Oceanic mean states and heat budget analysis for true positive and false negative marine heatwave events revealed that the model generally captures ocean advection dominated MHWs. Using SSHA as predictor variable, we find that our statistical model can forecast MHWs off southeast Tasmania up to 7 days in advance above random chance. This study provides improved understanding of the role of circulation anomalies associated with oceanic mesoscale eddies on MHWs off eastern Tasmania and highlights that individual MHWs in this region are potentially predictable up to 7 days in advance using mesoscale eddy-tracking methods.